Rise of the demon - Rowland, Diana, 1966- (DAW book collectors, 2022)
"Kara's drastic ceasefire deal with the formidable demon Imperator Dekkak slowed the attacks on Earth to a trickle, but her troubles are far from over. The god-like demahnk are desperate to return to their own kind, but unless they can stabilize the demon realm, they'll be forever exiled...One faction of demonic lords and demahnk has a plan to fix their world, yet their salvation would come at the expense of Earth"--